2020
DOI: 10.1007/s00226-020-01164-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of levoglucosenone obtained in analytical pyrolysis and screw-type reactor, separation and distillation

Abstract: This research is dedicated to the study on the formation of levoglucosenone and other main volatiles from the catalytic pyrolysis with the addition of phosphoric acid of birch wood and lignocelluloses obtained by birch wood hydrothermal treatment. Py-GC/MS/FID method was used to evaluate the contents of the main products. Lignocelluloses were found to be a more promising precursor to obtain levoglucosenone with lesser content of furfural: For birch wood and lignocelluloses hydrothermally treated at 150 and 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Softwood biomass also followed the same trend Furfural and HMF were co-products of the bio-oil, along with anhydrosugar, LGO, and other compounds. LGO, as well as furfural, HMF, LGA, and other undesirable compounds, were produced by phosphoric acid impregnation followed by hydrothermal processing [9]. Furanic platform chemicals such as furfural and HMF are seen as more environmentally friendly alternatives to petrochemicals.…”
Section: Feasibility Test Of the Small-scale Fluidized Bed Reactormentioning
confidence: 99%
See 3 more Smart Citations
“…Softwood biomass also followed the same trend Furfural and HMF were co-products of the bio-oil, along with anhydrosugar, LGO, and other compounds. LGO, as well as furfural, HMF, LGA, and other undesirable compounds, were produced by phosphoric acid impregnation followed by hydrothermal processing [9]. Furanic platform chemicals such as furfural and HMF are seen as more environmentally friendly alternatives to petrochemicals.…”
Section: Feasibility Test Of the Small-scale Fluidized Bed Reactormentioning
confidence: 99%
“…Unfortunately, this is outside the scope of this research. LGO using GC-MS analysis [9]. The conversion of birch wood for the synthesis of LGO was carried out using a screw-type pyrolysis reactor.…”
Section: Lu Et Al Computed Probable Chemical Routes From β-D-glucopyr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Levoglucosan has a commercial price, according to Sigma-Aldrich, of USD 110 g -1 and it is commonly used for the synthesis of high-value compounds and materials (esters, films, binders, UV polymers, and singular drugs) (Ermolenko, 2013). Recent studies have demonstrated the feasibility of extraction and subsequent distillation of levoglucosan from pyrolytic oil (Wang et al, 2016;Dobele et al, 2020). Hence, it is recommended to deepen in this subject, for optimization of levoglucosan production using pyrolysis plant at pilot level.…”
Section: No Retention Timementioning
confidence: 99%